Idiosyncratic tail risk and stock return in Indonesia - Iyvon Herliawan; Sung Suk Kim; Kie Van Ivanky Saputra; Ferry Vincenttius Ferdinand (Jurnal Keuangan dan Perbankan, 2020)
Idiosyncratic tail risk explains the financial crisis which happened due to idiosyncratic risk. It could also be used as a factor for asset pricing, making it necessary to be further studied since it could help protect investors from extreme incidents that could bring loss. We investigate the effect of idiosyncratic tail risk to the stock return in Indonesia. The data of daily stock price of 662 public companies in Indonesia that was registered in Indonesia stock exchange (IDX) are used during the period of 2006-2018. We include the firms that have at least 10 trading days in a month for providing enough observation to determine tail index to get idiosyncratic tail risk. First of all we using portfolio approach to find the effect of tail risks to the stock return is used. The results show that idiosyncratic tail risk has negative effects on the stock return in portfolio level. However, idiosyncratic tail risk does not have effects on stock return in individual firm level.JEL Classification: G12, G23 How to Cite:Murningsih, S., Firdaus, M., Purwanto, B. (2020). Factors influencing Indonesian rural banks’ credit disbursement. Jurnal Keuangan dan Perbankan, 24(2), 241-251.DOI: https://doi.org/10.26905/jkdp.v24i2.3778